Java programming for beginners learn the fundamentals of programming with Java - Lassoff, Mark (Packt Publishing, 2017)
Java Programming for Beginners is an introduction to Java programming, taking you through the Java syntax and the fundamentals of object-oriented programming. About This Book Learn the basics of Java programming in a step-by-step manner Simple, yet thorough steps that beginners can follow Teaches you transferable skills, such as flow control and object-oriented programming Who This Book Is For This book is for anyone wanting to start learning the Java language, whether you're a student, casual learner, or existing programmer looking to add a new language to your skillset. No previous experience of Java or programming in general is required. What You Will Learn Learn the core Java language for both Java 8 and Java 9 Set up your Java programming environment in the most efficient way Get to know the basic syntax of Java Understand object-oriented programming and the benefits that it can bring Familiarize yourself with the workings of some of Java's core classes Design and develop a basic GUI Use industry-standard XML for passing data between applications In Detail Java is an object-oriented programming language, and is one of the most widely accepted languages because of its design and programming features, particularly in its promise that you can write a program once and run it anywhere. Java Programming for Beginners is an excellent introduction to the world of Java programming, taking you through the basics of Java syntax and the complexities of object-oriented programming. You'll gain a full understanding of Java SE programming and will be able to write Java programs with graphical user interfaces that run on PC, Mac, or Linux machines. This book is full of informative and entertaining content, challenging exercises, and dozens of code examples you can run and learn from. By reading this book, you'll move from understanding the data types in Java, through loops and conditionals, and on to functions, classes, and file handling. The book finishes with a look at GUI development and training on how to work with XML. The book takes an efficient route through the Java landscape, covering all of the core topics that a Java developer needs. Whether you're an absolute beginner to programming, or a seasoned programmer approaching an object-oriented language for the first time, Java Programming for Beginners delivers the focused training you need to become a Java developer.